Do EU-wide stress tests affect insurers' dividend policies? - Petr Jakubik; Saida Teleu (Charles University in Prague, Institute of Economic Studies (IES), 2022)
The article employs panel data to investigate whether stress test results and other characteristics associated with European insurers vulnerabilities affect dividend distributions and share buybacks. We focus on the EU wide insurance stress test conducted in 2018 and 2021 as in this way we can also capture a behaviour of insurers during the COVID-19 crisis. Our empirical results suggest that two stress tests considered had no significant impact on changes in dividend distributions. However, more resilient insurers measured by assets-over-liabilities ratio seem to have higher dividend payout ratios including share buybacks. On the contrary, higher generated profit tend to be reflected in lower payout ratio.
Keywords: 330; dividend distributions; dividends and share buybacks; European insurers; EU-wide insurance stress test; COVID-19